Honokiol Induces Apoptosis, G1 Arrest, and Autophagy in KRAS Mutant Lung Cancer Cells - Luo, Lian-Xiang; Li, Ying; Liu, Zhong-Qiu; Fan, Xing-Xing; Duan, Fu-Gang; Li, Run-Ze; Yao, Xiao-Jun; Leung, Elaine Lai-Han; Liu, Liang (Frontiers in Pharmacology, 2017)
Aberrant signaling transduction induced by mutant KRASproteins occurs in 20 30% of non-small cell lung cancer (NSCLC), however, a direct and effective pharmacological inhibitor targeting KRAS has not yet reached the clinic to date. Honokiol, a small molecular polyphenol natural biophenolic compound derived from the bark of magnolia trees, exerting anticancer activity, however, its mechanism remains unknown. In this study, we sought to investigate the in vitro effects of honokiol on NSCLC cell lines harboring KRAS mutations. Honokiol was shown to induce G1 arrest and apoptosis to inhibit the growth of KRAS mutant lung cancer cells, which was weakened by an autophagy inhibitor 3-methyladenine (3-MA), suggesting a pro-apoptotic role of honokiol–induced autophagy that was dependent on AMPK-mTOR signaling pathway. In addition, we also discovered that Sirt3 was significantly up-regulated in honokiol treated KRAS mutant lung cancer cells, leading to destabilization of its target gene Hif-1α, which indicated that the anticancer property of honokiol maybe regulated via a novel mechanism associated with the Sirt3/Hif-1α. Taken together, these results broaden our understanding of the mechanisms on honokiol effects in lung cancer, and reinforce the possibility of its potential anticancer benefit as a popular Chinese herbal medicine (CHM).